Representaciones Sociales de las Víctimas del Conflicto Armado Residentes en el Quindío Sobre la Reparación Integral (2011)
In Colombia, armed conflict has left 7,999,663 victims of which 32,258 reside in Quindio; because of the consequences that war has left these people, in 2011 the 1448 law governing the repair processes that aim to solve the needs of these victims was established. In this context, the present descriptive qualitative research aimed to describe cutting the contents of the social representations of victims of armed conflict against full compensation in the department of Quindio. To do these ten victims who reside properly in the municipalities of La Tebaida, Calarca, Genoa and Armenia an interview whose structured questionnaire was worth 20 questions through which pertinent questions were asked as to repair material and symbolic reparation was applied. The qualitative analysis of the data shows that victims despite access processes material reparation deeply distrustful of the bodies in charge despite not access processes symbolic reparation, are clear about what they could repair symbolically so manifest that neither the media, and civil society are carrying this out, besides this, the victims expressed that although full reparation processes are useful, not return anything the war has taken from them.